The pledge - Derting, Kimberly (Derting, Kimberly. Pledge novel., 2011)
In a dystopian kingdom where the classes are separated by the languages they speak, Charlaina "Charlie" Hart has a secret gift that is revealed when she meets a mysterious young man named Max.